Prevalence of atrial fibrillation in elderly subjects (the Cardiovascular Health Study). - Furberg, C D; Psaty, B M; Manolio, T A; Gardin, J M; Smith, V E; Rautaharju, P M (Am J Cardiol, 1994)
Atrial fibrillation (AF) is a common arrhythmia in elderly persons and a common cause of embolic stroke. Most studies of the prevalence and correlates of AF have used selected, hospital-based populations. The Cardiovascular Health Study is a population-based, longitudinal study of risk factors for coronary artery disease and stroke in 5,201 men and women aged > or = 65 years. AF was diagnosed in 4.8% of women and in 6.2% of men at the baseline examination, and prevalence was strongly associated with advanced age in women. Prevalence of AF was 9.1% in men and women with clinical cardiovascular disease, 4.6% in patients with evidence of subclinical but no clinical cardiovascular disease, and only 1.6% in subjects with neither clinical nor subclinical cardiovascular disease. A history of congestive heart failure, valvular heart disease and stroke, echocardiographic evidence of enlarged left atrial dimension, abnormal mitral or aortic valve function, treated systemic hypertension, and advanced age were independently associated with the prevalence of AF. The low prevalence of AF in the absence of clinical and subclinical cardiovascular disease calls into question the existence and clinical usefulness of the concept of so-called "lone atrial fibrillation" in the elderly.
Keywords: Aged; Aged, 80 and over; Anti-Arrhythmia Agents; Anticoagulants; Atrial Fibrillation; Blood Glucose; Cardiovascular Diseases; Chi-Square Distribution; Coronary Disease; Electrocardiography; Female; Humans; Male; Prevalence; Regression Analysis; Sampling Studies

Reduced vital capacity in elderly persons with hypertension, coronary heart disease, or left ventricular hypertrophy. The Cardiovascular Health Study. - Enright, P L; Kronmal, R A; Smith, V E; Gardin, J M; Schenker, M B; Manolio, T A (Chest, 1995)
The Cardiovascular Health Study provided the opportunity to determine the association of subclinical and clinical cardiovascular disease with pulmonary function in a population sample of elderly adults. Included were 2,955 women and 2,246 men over age 64 years who were recruited for this observational study from four communities and completed extensive examinations that included spirometry, echocardiograms, and blood pressure. Current smokers, past smokers with >20 pack-years of smoking, and persons with a history of asthma, chronic bronchitis, or emphysema were excluded from this analysis, leaving 2,784 (55%) of the cohort. Systolic hypertension or coronary artery disease was associated with 40- to 100-mL decrements in FEV1, and 50- to 150-mL decrements in FVC, while a history of congestive heart failure was associated with 200 to 300 mL lower FEV1 and FVC values (p < 0.0001), after correcting for age, height, and waist size. Higher left ventricular (LV) mass was also significantly associated with a decrease in FEV1 and FVC in multivariate models. This relationship was strongest with the end-diastolic LV posterior wall thickness component of LV mass. In summary, FEV1 and FVC are reduced in elderly persons with hypertension, ischemic heart disease, higher disease, higher LV mass, and congestive heart failure, though the magnitude of these associations is relatively small unless heart failure supervenes. Substantial decrements in percent predicted FEV1 and FVC should not be attributed to the presence of uncomplicated ischemic heart disease or hypertension alone.
Keywords: Age Factors; Aged; Aged, 80 and over; Coronary Disease; Female; Forced Expiratory Volume; Humans; Hypertension; Hypertrophy, Left Ventricular; Male; Middle Aged; Ventricular Function, Left; Vital Capacity

Sex, age, and disease affect echocardiographic left ventricular mass and systolic function in the free-living elderly. The Cardiovascular Health Study. - Gardin, J M; Siscovick, D; Anton-Culver, H; Lynch, J C; Smith, V E; Klopfenstein, H S; Bommer, W J; Fried, L; O'Leary, D; Manolio, T A (Circulation, 1995)
BACKGROUND: Left ventricular (LV) hypertrophy, as measured by M-mode echocardiography, is an independent predictor of mortality and/or morbidity from coronary heart disease (CHD). LV global and segmental systolic dysfunction also have been associated with myocardial ischemia and cardiovascular morbidity and mortality. Echocardiographic data, especially two-dimensional, have not been available previously from multicenter-based studies of the elderly. This report describes the distribution and relation at baseline of echocardiographic LV mass and global and segmental LV wall motion to age, sex, and clinical disease category in the Cardiovascular Health Study (CHS), a cohort of 5201 men and women (4850 white) 65 years of age and older. METHODS AND RESULTS: M-mode LV mass adjusted for body weight increased modestly with age (P < .0001), increasing less than one gram per year increase in age for both men and women. After adjustment for weight, LV mass was significantly greater in men than in women and in participants with clinical CHD compared with participants with neither clinical heart disease nor hypertension (both P < .001). Across all CHS age subgroups, the difference in weight-adjusted LV mass by sex was greater in magnitude than the difference related to clinical CHD. M-mode measurements of LV mass could not be made in 34% of CHS participants, and this was highly related to age (29% in the 65 to 69 year versus 50% in the 85+ year age group, P < .001) and other risk factors. In participants with clinical CHD and with neither clinical heart disease nor hypertension, LV ejection fraction and segmental wall motion abnormalities were more prevalent in men than women (all P < .001). Of interest, 0.5% of men and 0.4% of women with neither clinical heart disease nor hypertension had LV segmental wall motion abnormalities, suggesting silent disease, compared with 26% of men and 10% of women in the clinical CHD group (P < .0001). Multivariate analyses revealed male sex and presence of clinical CHD (both P < .001) to be independent predictors of LV akinesis or dyskinesis. CONCLUSIONS: Significant baseline relations were detected between differences in sex, prevalent disease status, and echocardiographic measurements of LV mass and systolic function in the CHS cohort. Age was weakly associated with LV mass measurements and LV ejection fraction abnormalities. These relations should be considered in evaluating the preclinical and clinical effects of CHD risk factors in the elderly.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cohort Studies; Coronary Disease; Echocardiography; Female; Humans; Hypertrophy, Left Ventricular; Male; Sex Factors; Systole

Carotid artery measures are strongly associated with left ventricular mass in older adults (a report from the Cardiovascular Health Study). - Kronmal, R A; Smith, V E; O'Leary, D H; Polak, J F; Gardin, J M; Manolio, T A (Am J Cardiol, 1996)
Associations of carotid artery diameter and intimal-medial thickness by ultrasound with echocardiographic left ventricular (LV) structure were examined in 3,409 participants in the Cardiovascular Health Study, a population-based study of risk factors for coronary heart disease and stroke in men and women aged > or = 65 years. At baseline, sector-guided M-mode echocardiography and B-mode ultrasound were used to evaluate the left ventricle and carotid arteries, respectively. Common carotid artery diameter and intimal-medial thickness were significantly related to LV mass in correlational analysis (r=0.40 and 0.20, respectively, p<0.01), and each was independently associated with LV mass after adjustment for age, gender, weight, systolic and diastolic blood pressure, antihypertensive medication use, prior coronary heart disease, electrocardiographic abnormalities, high-density lipoprotein, and factor VII. We speculate that changes in the arterial wall affect impedance to LV ejection leading to increases in LV mass. Further follow-up of this cohort is in progress and will help to determine whether such carotid artery measures could, by exacerbating LV hypertrophy, constitute another important risk factor for adverse cardiovascular outcomes.
Keywords: Aged; Carotid Arteries; Cohort Studies; Female; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; Risk Factors; Ultrasonography

Clinical factors associated with calcific aortic valve disease. Cardiovascular Health Study. - Stewart, B F; Siscovick, D; Lind, B K; Gardin, J M; Gottdiener, J S; Smith, V E; Kitzman, D W; Otto, C M (J Am Coll Cardiol, 1997)
OBJECTIVES: The aim of this study was to determine the prevalence of aortic sclerosis and stenosis in the elderly and to identify clinical factors associated with degenerative aortic valve disease. BACKGROUND: Several lines of evidence suggest that degenerative aortic valve disease is not an inevitable consequence of aging and may be associated with specific clinical factors. METHODS: In 5,201 subjects > or = 65 years of age enrolled in the Cardiovascular Health Study, the relation between aortic sclerosis or stenosis identified on echocardiography and clinical risk factors for atherosclerosis was evaluated by using stepwise logistic regression analysis. RESULTS: Aortic valve sclerosis was present in 26% and aortic valve stenosis in 2% of the entire study cohort; in subjects > or = 75 years of age, sclerosis was present in 37% and stenosis in 2.6%. Independent clinical factors associated with degenerative aortic valve disease included age (twofold increased risk for each 10-year increase in age), male gender (twofold excess risk), present smoking (35% increase in risk) and a history of hypertension (20% increase in risk). Other significant factors included height and high lipoprotein(a) and low density lipoprotein cholesterol levels. CONCLUSIONS: Clinical factors associated with aortic sclerosis and stenosis can be identified and are similar to risk factors for atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Calcinosis; Female; Heart Valve Diseases; Humans; Male; Prospective Studies; Risk Factors; Sclerosis

Diabetes mellitus and echocardiographic left ventricular function in free-living elderly men and women: The Cardiovascular Health Study. - Lee, M; Gardin, J M; Lynch, J C; Smith, V E; Tracy, R P; Savage, P J; Szklo, M; Ward, B J (Am Heart J, 1997)
This report describes the relation among diabetes, blood pressure, and prevalent cardiovascular disease, and echocardiographically measured left ventricular mass and filling (transmitral valve flow) velocities in the Cardiovascular Health Study, a cohort of 5201 men and women > or = 65 years of age. Ventricular septal and left posterior wall thicknesses were greater in diabetic than in nondiabetic subjects, showing a significant linear trend (p = 0.025 for ventricular septal thickness in both sexes combined, p = 0.002 for posterior wall thickness) with increased duration of diabetes. Increased wall thickness of the ventricular septum or the left posterior wall was not associated with prevalent coronary heart disease (CHD) in the cohort. Increased left ventricular mass was associated with diabetic persons not reporting CHD and with all subjects with CHD regardless of glucose tolerance status. After adjusting for body weight, blood pressure, heart rate, and prevalent coronary or cerebrovascular disease, diabetes (as measured by glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination) remained an independent predictor of increased left ventricular mass among men and women (174.2 gm in diabetic men vs 169.8 gm in normal men, 138.2 gm in diabetic women vs 134.0 gm in normal women, p = 0.043 for both sexes combined). Both early and late diastolic transmitral peak flow velocities were higher with increased duration of diabetes, but the calculated ratio of the early peak flow velocity to the late velocity (E/A ratio) did not differ significantly between subjects with historical diabetes and those with normal fasting glucose (both genders combined, p = 0.190). Glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination were significant independent predictors of the late transmitral peak flow velocity and its integrated flow-velocity curve but not for the integral of the early peak flow velocity or the E/A ratio. Diabetes is associated with abnormal left ventricular structure and function in elderly persons. This association persists after adjustment for body weight, blood pressure, heart rate, and reported coronary or cerebrovascular disease.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Diabetes Mellitus; Echocardiography; Female; Glucose Tolerance Test; Humans; Male; Mitral Valve; Residence Characteristics; Ventricular Function, Left

Left ventricular diastolic filling in the elderly: the cardiovascular health study. - Gardin, J M; Arnold, A M; Bild, D E; Smith, V E; Lima, J A; Klopfenstein, H S; Kitzman, D W (Am J Cardiol, 1998)
Changes in left ventricular (LV) diastolic function (e.g., as measured by transmitral flow velocity) are known to occur with aging. In addition, impaired LV diastolic function plays an important role in such cardiovascular disorders common in the elderly as hypertension, ischemic heart disease, and congestive heart failure (CHF). Participants in the Cardiovascular Health Study, a multicenter study of community-dwelling men (n=2,239) and women (n=2,962) > or = 65 years of age, underwent an extensive baseline evaluation, including echocardiography. Early diastolic LV Doppler (transmitral) peak filling velocity decreased, and peak late diastolic (atrial) velocity increased with age in multivariate analyses (all p <0.001). Early and late diastolic peak filling velocities were both significantly higher in women than in men, even after adjustment for body surface area (or height and weight). In multivariate models in the entire cohort and a healthy subgroup (n=703), gender, age, heart rate, and blood pressure (BP) were most strongly related to early and late diastolic transmitral peak velocities. Early and late diastolic peak velocities both increased with increases in systolic BP and decreased with increases in diastolic BP (p <0.001). Doppler transmitral velocities were compared among health status subgroups. In multiple regression models adjusted for other covariates, and in analysis of variance models examining differences across subgroups adjusted only for age, the subgroup with CHF had the highest early diastolic peak velocities. All clinical disease subgroups had higher late diastolic peak velocities than the healthy subgroup, with the subgroups with either CHF or hypertension having the highest age-adjusted means. The subgroup with hypertension had the lowest ratio of early-to-late diastolic peak velocity, and men with CHF had the highest ratio. These findings are consistent with previous reports that hypertensive subjects exhibit an abnormal relaxation pattern, whereas patients with CHF develop a pattern suggestive of an increased early diastolic left atrial-LV pressure gradient.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Blood Flow Velocity; Cardiovascular Diseases; Cohort Studies; Diastole; Echocardiography, Doppler; Electrocardiography; Female; Health Status; Heart Ventricles; Humans; Male; Ventricular Function, Left

M-mode echocardiographic predictors of six- to seven-year incidence of coronary heart disease, stroke, congestive heart failure, and mortality in an elderly cohort (the Cardiovascular Health Study). - Gardin, J M; McClelland, R; Kitzman, D; Lima, J A; Bommer, W; Klopfenstein, H S; Wong, N D; Smith, V E; Gottdiener, J (Am J Cardiol, 2001)
Previous studies have identified a number of echocardiographic variables that predict cardiovascular disease (CVD) events and mortality, but have not focused on a large elderly cohort. The purpose of this study was to determine whether M-mode echocardiographic variables predicted all-cause mortality, incident coronary heart disease (CHD), congestive heart failure (CHF), and stroke in a large prospective, multicenter, population-based study. In the Cardiovascular Health Study, a biracial cohort of 5,888 men and women (mean age 73 years) underwent 2-dimensional M-mode echocardiographic measurements of left ventricular (LV) internal dimensions, wall thickness, mass and geometry, as well as measurement of left atrial dimension and assessment for mitral annular calcium. Participants were followed for 6 to 7 years for incident events; analyses excluded subjects with prevalent disease. One or more echocardiographic measurements were independent predictors of all-cause mortality and incident CHD, CHF, and stroke. After adjustment for anthropometric and traditional CVD risk factors, LV mass was significantly related to incident CHD, CHF, and stroke. The highest quartile of LV mass conferred a hazards ratio of 3.36, compared with the lowest quartile, for incident CHF. Furthermore, incident CHF-free survival was significantly lower for participants with LV mass in the highest versus the 2 lowest quartiles (86% vs 97%, respectively, at 2,500 days). Eccentric and concentric LV hypertrophy, respectively, conferred adjusted hazards ratios, compared with normal LV geometry, of 2.05 and 1.61 for incident CHD, and 2.95 and 3.32 for incident CHF. Thus, in an elderly biracial population, selected 2-dimensional M-mode echocardiographic measurements were important markers of subclinical disease and conferred independent prognostic information for incident CVD events, especially CHF and CHD.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Coronary Disease; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke